Clinical Characteristics of Aldosterone- and Cortisol-Coproducing Adrenal Adenoma in Primary Aldosteronism. (25th March 2018) - Tang, Lu; Li, Xintao; Wang, Baojun; Ma, Xin; Li, Hongzhao; Gao, Yu; Gu, Liangyou; Nie, Wenyuan; Zhang, Xu
Abstract : Aldosterone- and cortisol-coproducing adrenal adenoma (A/CPA) cases have been observed in patients with primary aldosteronism (PA). This study investigated the incidence, clinical characteristics, and molecular biological features of patients with A/CPAs. We retrospectively identified 22 A/CPA patients from 555 PA patients who visited the Chinese People's Liberation Army General Hospital between 2004 and 2015. Analysis of clinical parameters revealed that patients with A/CPAs had larger tumors than those with pure APAs (P < 0.05 ). Moreover, they had higher proportions of cardiovascular complications, glucose intolerance/diabetes, and osteopenia/osteoporosis compared to the pure APA patients (P < 0.001 ). In the molecular biological findings, quantitative real-time PCR analysis revealed similar CYP11B1 and CYP17A1 mRNA expressions in resected A/CPA specimens and in pure APA specimens. Western blot and immunochemical analyses showed CYP11B1, CYP11B2, and CYP17A1 expressions in both A/CPAs and pure APAs. Seventeen cases with KCNJ5 mutations were detected among the 22 A/CPA DNA samples, but no PRKACA or other causative mutations were observed. Each patient improved following adrenalectomy. In conclusion, A/CPAs were not rare among PA patients. These patients associated with high incidences of cardiovascular events and metabolic disorders. Screening for excess cortisol secretion is necessary for PA patients.